2007
DOI: 10.1111/j.1752-0606.2007.00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Disarming People With Words: Strategies of Interactional Communication That Crisis (Hostage) Negotiators Share With Systemic Clinicians

Abstract: This qualitative study examined the interactional communication strategies used by law enforcement officers during a hostage-taking incident at a high school. The research involved analysis of the negotiation conversation between police crisis (hostage) negotiators and a hostage taker who entered his former high school to take revenge on a teacher. A condensed version of the talk was micro-analyzed with the actual negotiators from the incident, using ethnographic and Interpersonal Process Recall interviewing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…At the same time, our understanding of suicide—from cause to prevention—has evolved in psychological and medical domains, often in overlap with the crisis negotiation literature. As Charlés () notes, “hostage incidents are not the primary type of critical incident with which crisis negotiators deal … Rather, negotiators often face people in the midst of an escalated personal crisis” (p. 52). In the UK and USA, police negotiators work and are trained from Hostage and Crisis Units, and their remit incorporates crisis communication in hostage, terrorism, and suicide situations.…”
Section: The Language Of Crisis Negotiationmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, our understanding of suicide—from cause to prevention—has evolved in psychological and medical domains, often in overlap with the crisis negotiation literature. As Charlés () notes, “hostage incidents are not the primary type of critical incident with which crisis negotiators deal … Rather, negotiators often face people in the midst of an escalated personal crisis” (p. 52). In the UK and USA, police negotiators work and are trained from Hostage and Crisis Units, and their remit incorporates crisis communication in hostage, terrorism, and suicide situations.…”
Section: The Language Of Crisis Negotiationmentioning
confidence: 99%
“…Negotiators deal with crises of various kinds, including hostage‐taking and terrorism, as well as personal crises of the kind we examine in this paper. The latter is most common yet least studied (Charlés, ). We will also examine the limited body of work that examines how secondary parties intervene in conversations between a different primary party and their interlocutor (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In late 1980's, a turning point in literature occurred when Stevens and MacKenna (1988) published a Special Weapons and Tactic study. In concert with their scholarship, numerous publications addressing attributes correlated with successful hostage negotiators appeared (Tatar 1983;Gelbart 1997;Royce 2005;Miller and Clark 2006;Strentz 2006;Van Hasselt et al 2006;Charlés, 2007;Donohue and Taylor 2007;Van Hasselt, Romano, and Vecchi 2008). Scholarship from 1988 forward frequently provided descriptions of offender characteristics and incidents.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-eight years after Stevens and MacKenna's 1988 findings, assessment tools for selection of Department of Defense Special Forces operators and Law Enforcement SWAT candidates had advanced including methods assessing reasoning ability and impulse control when stimulated with visual and auditory distractors in addition to escalating stress (Hirsch, 2017). Review of literature revealed numerous publications addressing attributes correlated with successful hostage negotiators (Charlés, 2007;Donohue & Taylor, 2007;Gelbart, 1997;Miller & Clark, 2006;Royce, 2005;Strentz, 2006;Tatar, 1983;Van Hasselt et al, 2006;Van Hasselt, Romano, and Vecchi, 2008). Stevens and MacKenna (1988) reported few SWAT members had skills in forensic laboratory analysis, handwriting analysis, bomb disposal, foreign language skills, intelligence analysis, and bomb detection.…”
Section: View Of Swatmentioning
confidence: 99%
“…I appreciate the opportunity to respond to Gale’s (this issue) comments regarding my study of hostage negotiation discourse, an excerpted version of which appears in this issue of JMFT (Charlés, this issue). I have studied Gale’s work for many years and, as a researcher and supervisor of marriage and family therapy (MFT), have found his methodological approaches to examining what therapy discourse looks like “in the room” extremely valuable.…”
mentioning
confidence: 99%